PERBEDAAN TINGKAT TEKANAN DARAH SEBELUM DAN SESUDAH DILAKUKAN TINDAKAN AKUPRESUR PADA PENDERITA HIPERTENSI LANSIA DI PSLU PUGER KABUPATEN JEMBER - Eko Bagus Santoso (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2015)
Problem of hypertension in the elderly is often found to be a major factor for coronary disease. Elderly In Social Institution Puger Jember, there are number of elderly who suffer from hypertension as much as 50%. Penatalaksaan hypertension in the elderly is essential to lower blood pressure by pharmacological therapy and non-pharmacological therapy. One of the non-pharmacological therapy in hypertension by using acupressure. The purpose of the study was to determine differences in the level of blood pressure before and after the act of acupressure in elderly hypertensive patients in PSLU Puger Jember. Pre-experimental research design plan design with one group pretest-posttest design. The population in this study as many as 70 people. The sampling technique used is random sampling. According to the experimental sample size Roscoe number of sample members 10 s / d 20, then obtained a sample of 14 people. The results showed that prior to the act of acupressure most respondents have a category of blood pressure levels as much as level 1 (64.3%). Most respondents after acupressure action has a category 1 level of blood pressure levels as much (85.7%). Based on the analysis of matched pairs Wilcoxon test p value = 0.083, p value (<0.05). It can be concluded that Ho accepted levels of blood pressure before and after the action of acupressure are the same. Suggestions for further research should be very familiar with the mechanism of implementation acupressure meridian points are pressed to the right and lead to positive outcomes for the elderly.